Exploring genotype-by-environment interactions: impacts on genome-wide association and genomic prediction for 30 white spruce traits related to productivity, defense, and climate-adaptability - Cappa, Eduardo Pablo (2024)
White spruce (Picea glauca (Moench) Voss) is considered a keystone species in boreal forest ecosystems and a valuable resource for the commercial timber industry. White spruce is also known for its adaptability to diverse growth, and stress resilience is essential, especially in the context of a changing climate. Genome-wide association studies (GWAS) and genomic prediction (GP) are potent tools for understanding complex traits in forest trees. However, their application to genotype-by-environment interactions in white spruce remains limited, highlighting a research gap in forest tree genetics. We conducted a comprehensive multi-environmental GWAS and GP analysis for 30 productivity, defense, and climate-adaptability traits assessed on 1,540 white spruce trees from central Alberta, Canada, genotyped for 467,224 SNP markers, and growing across three environments.